Suicide Attempt with Rodenticide Including Zinc Phosphide Case Report - Yıldız, İsa; Akgül, Sibel; Özkan, Süreyya; Güneş, Hacı Yusuf; Bayır, Hakan; Özdeş, Taşkın (The Bulletin of Legal Medicine, 2015)
Zinc phosphide is a toxic chemical agent used as a rodenticide. The effects are on heart, lung, kidney and gastrointestinal tract. Metabolic acidosis, high amylase, liver damage, hypotension, shock and cardiac arrhythmia is observed. Forty-year-old male patientevaluated with a history of taking zinc phosphide containing rat poison inorder to commit suicide. Respiratory distress, arrhythmias, commonly involuntary muscle contraction, metabolic acidosis, coagulation disorders, amylase, AST and LDH levels were determined. Term follow-up after intensive care unit and was discharged favor. In this paper, for the purpose of suicide zinc phosphide our experiences in the field of public information in the cases of ICU follow-up treatment process is intended to share the accompaniment.
Keywords: rodenticide; zinc phosphide; suicide; metabolic acidosis; high amylase